COVID-19 phobia in a boy with undiagnosed autism spectrum disorder: A case report. Issue 22 (4th June 2021) - Sakamoto, Shoko; Miyawaki, Dai; Goto, Ayako; Harima, Yuji; Tokuhara, Daisuke; Inoue, Koki
Abstract: Rationale: Coronavirus disease 2019 (COVID-19) is affecting mental health profoundly. Previous studies have reported pandemic-related anxiety. Anxiety disorder and autism spectrum disorder (ASD) are common comorbidities. However, there has been no report of any patient with undiagnosed ASD who developed anxiety disorders caused by the COVID-19 pandemic. In this case report, we describe an 8-year-old Japanese boy with undiagnosed ASD who developed COVID-19 phobia, resulting in avoidant restrictive food intake disorder (ARFID). Patient concerns: As COVID-19 was highly publicized in the mass media and the risk of droplet infection was emphasized upon, the patient began to fear viral contamination from food, culminating in a refusal to eat or even swallow his saliva. He was admitted to a pediatric medical center in Osaka with life-threatening dehydration and was then referred to our child psychiatry department. Diagnosis: We diagnosed the patient with COVID-19 phobia resulting in ARFID. We identified ASD traits from his present social communication skills and developmental history. Interventions: We provided psychoeducation of ASD for the parents and administered supportive psychotherapy. Outcomes: Shortly after our intervention to relieve his ASD-related anxiety, his dysphagia improved. Lessons: Our findings suggest that children with undiagnosed ASD may develop COVID-19 phobia. In these cases, intervention for ASD may be more appropriate than starting treatment for anxiety disorders as the first-line option. COVID-19 is the biggest pandemic in the recent past, and more undiagnosed ASD patients who develop COVID-19 phobia may seek treatment. Clinicians should consider the underlying ASD in these patients and assess their developmental history and present social communication skills.